Huddle cam HD air / Muhammad Basri Yahaya ... [et al.] - Yahaya, Muhammad Basri; Anuar, Muhammad Afizi; Hasbullah, Hurairah; Kamal Abdul Ali, Fadzila Filza; Azhar Ahmad, Nurintan Elisa; Sallehuddin, Nors Yaza Amirah (2017)
Huddle cam Sdn. Bhd. is a new company that develops a portable solar cooling powered device together with security camera system. Through observations, most cars in Malaysia are faced the same problem which is the temperature inside the car will be increased when the engine is switch off. It is common for drivers to park their cars at open spaced parking our underground parking. Both places are exposing the cars to extreme heat and there is always the risk of cars theft. Thus, the invention of this device is prioritizing the users comfort and at the same time, it provides a security to the cars.